М
Молодежь
К
Компьютеры-и-электроника
Д
Дом-и-сад
С
Стиль-и-уход-за-собой
П
Праздники-и-традиции
Т
Транспорт
П
Путешествия
С
Семейная-жизнь
Ф
Философия-и-религия
Б
Без категории
М
Мир-работы
Х
Хобби-и-рукоделие
И
Искусство-и-развлечения
В
Взаимоотношения
З
Здоровье
К
Кулинария-и-гостеприимство
Ф
Финансы-и-бизнес
П
Питомцы-и-животные
О
Образование
О
Образование-и-коммуникации
Serpopi
Serpopi
21.12.2021 00:34 •  Алгебра

Решите систему уравнений а)1/x- 1/y=1/6 x-y = -1 b) 1/x+ 1/y=1/6 x+y=1

👇
Ответ:
ilya429
ilya429
21.12.2021
А
{1/x- 1/y=1/6⇒6(y-x)=xy
{x-y = -1 ⇒y=x+1
6(x+1-x)=x²+x
x²+x-6=0
x1+x2=-1 U x1*x2=-6
x1=-3⇒y1=-3+1=-2
x2=2⇒y2=2+1=3
(-3;-2);(2;3)
b
{1/x+ 1/y=1/6⇒6(x+y)=xy
{x+y=1 ⇒x=1-y
6-y+y²=0
D=1-24=-23 нет решения
4,6(59 оценок)
Открыть все ответы
Ответ:
Olzhas2889
Olzhas2889
21.12.2021

ответ: 1) x = (a + b) / (a - b);   a ≠ b;  2)  x = 2 · (m - n); 3)  x = a + 1;

4) x = (3 · (m - n)) / (m + n);  m ≠ - n  

Объяснение:

1) a²x - b²x = a² + 2ab + b²;   x · (a - b) · (a + b) = (a + b)²;  x = (a + b)² / (a - b) · (a + b)

x = (a + b) / (a - b);   a ≠ b

2) 3mx + 3nx = 6m² - 6n²;   3 · x · (m + n) = 6 · (m + n) · (m - n);  

x = (6 · (m + n) · (m - n)) / 3 · (m + n);  x = 2 · (m - n)

3) ax + x = a² + 2a + 1;  x · (a + 1) = (a + 1)²;   x = (a + 1)² / (a + 1) = a + 1;  x = a + 1

4) m²x + 2mnx + n²x = 3m² - 3n²;    x · (m + n)² = 3 · (m + n) · (m - n);

x = (3 · (m + n) · (m - n)) / (m + n)²;   x = (3 · (m - n)) / (m + n);  m ≠ - n  

4,7(27 оценок)
Ответ:
ania51
ania51
21.12.2021

ответ:

объяснение:

f(x)=x³-27x

1)  f `(x)=(x³-27x)`=3x²-27=3(x²-9)=3(x-3)(x+3)

2) f `(x)=0 при  3(x-3)(x+3)=0

                            x=3   v   x=-3

                +                       -                     +

-

                ↑                       ↓                       ↑

f(x) - возрастает на (-∞; -3)u(3; +∞)

f(x)- убывает на (-3; 3)

4,4(44 оценок)
logo
Вход Регистрация
Что ты хочешь узнать?
Спроси Mozg
Открыть лучший ответ